Sexuality and subordination : interdisciplinary studies of gender in the nineteenth century - Mendus, Susan; Rendall, Jane, 1945- (Routledge, 1989)
Using insights from history, literature, sociology and philosophy, Sexuality and Subordination examines the construction of gender in nineteenth century Britain and France.